2014
DOI: 10.1155/2014/787498
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of CD117-Immunocytochemistry Staining Patterns to Mutational Exon-11 inc-kitDetected by PCR from Fine-Needle Aspirated Canine Mast Cell Tumor Cells

Abstract: Canine cutaneous mast cell tumors (MCT) are the lethal skin tumors. The biological behavior of the MCT cells is quite varied and unpredictable. Almost MCT dogs usually require a rapid diagnosis and therapy. However, MCT diagnosis and prognosis are still dependent on histopathology which is rather inconvenient, time-consuming, painful, and harmful for some cases. Indeed, MCT can be easily accessible using fine-needle aspiration (FNA). In this study, our biopsy specimens were classified as low- and high-grade MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
2
17
0
1
Order By: Relevance
“…Some intermediate-grade tumors have a benign behavior, while others exhibit aggressive growth and a high frequency of local and distant recurrence [23]. CD117 (KIT) is a tyrosine kinase receptor protein expressed on the surface of bone marrow precursors (myeloid, erythroid, mouse but not human pro B-blast and pro T-blast cells) and mature mast cells [25][26][27], and it is a useful marker in the diagnosis of mast cell disorders and gastrointestinal stromal tumors [26].…”
Section: Introductionmentioning
confidence: 99%
“…Some intermediate-grade tumors have a benign behavior, while others exhibit aggressive growth and a high frequency of local and distant recurrence [23]. CD117 (KIT) is a tyrosine kinase receptor protein expressed on the surface of bone marrow precursors (myeloid, erythroid, mouse but not human pro B-blast and pro T-blast cells) and mature mast cells [25][26][27], and it is a useful marker in the diagnosis of mast cell disorders and gastrointestinal stromal tumors [26].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of genetic factors cannot be excluded either. The presence of a c-kit gene mutation in the nuclear genome in mast cell tumours with a higher malignancy grade has been reported (Zemke et al 2002, Sailasuta et al 2014. Moreover, as demonstrated by Zemke et al 2002, there was no relationship between the presence of the mutation and the Epidemiological study of canine mast cell tumours...dog's breed.…”
Section: Discussionmentioning
confidence: 97%
“…C-kit mutations are mostly the characteristic of CMCTs of higher histological grade [9,15,23,24]. It has been suggested that these mutations play a role in the malignant transformation of CMCTs [24].…”
Section: Discussionmentioning
confidence: 99%